Improving the diagnosis of nonfunctional overreaching and overtraining syndrome - Buyse, L.; Decroix, L.; Timmermans, N.; Barbé, K.; Verrelst, R.; Meeusen, R. (Medicine & Science in Sports & Exercise, 2019)
This study aimed to simplify and optimize the distinction between nonfunctional overreaching (NFO) and overtraining syndrome (OTS) by developing a multivariate approach (discriminant analysis [DA]) including hormonal and psychological changes measured during the Training Optimization (TOP) test. Methods Sensitivity of previously defined cutoff values for hypothalamic-pituitary-adrenal axis hormonal changes were recalculated on a larger database (n = 100). Discriminant analysis including hormonal and psychological variables measured during the TOP test was used to discriminate between NFO and OTS and predict the diagnosis of new cases.